(untitled) - Miser, Brad L. (Indianapolis, IN, 2012)
In this book includes savvy advice and plenty of no-nonsense information in a clear layout that is easy to access. Covers essential tools, topics, and shortcuts on things like desktop sharing, wireless networking, running Windows applications, using the Intel Ivy Bridge processor, and more.Features Genius icons throughout the book that provide smart and innovative ways to handle tasks and save yourself time
Keywords: Mạng và mạng không dây,Internet and wireless